1975
DOI: 10.1038/bjc.1975.69
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of human cells by SV40 virus

Abstract: Fibroblast cultures were prepared from skin biopsies from 29 patients and tested for their susceptibility to transformation by simian virus SV40. Cells with a normal chromosome complement showed a mean transformation frequency of 25/106 cells but for cells from a single patient with Fanconi's anaemia, the value was 152/106 cells. An increased susceptibility to transformation was observed for cells from 6 patients with Down's syndrome 3 patients with trisomy 18, a patient with trisomy 18 for 5% of cells and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Todaro and co-workers (1) reported that skin fibroblasts derived from Fanconi anemia patients exhibited a higher incidence of colony or focus formation (transformation) than cells from normal individuals following infection with simian virus 40 (SV40) in vitro. This finding has been confirmed in other laboratories (2)(3)(4)(5). It was postulated that SV40 transformation may represent an in vitro marker for high cancer risk in genetic disorders such as Fanconi anemia and Down's syndrome (6).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Todaro and co-workers (1) reported that skin fibroblasts derived from Fanconi anemia patients exhibited a higher incidence of colony or focus formation (transformation) than cells from normal individuals following infection with simian virus 40 (SV40) in vitro. This finding has been confirmed in other laboratories (2)(3)(4)(5). It was postulated that SV40 transformation may represent an in vitro marker for high cancer risk in genetic disorders such as Fanconi anemia and Down's syndrome (6).…”
Section: Introductionsupporting
confidence: 64%
“…It was postulated that SV40 transformation may represent an in vitro marker for high cancer risk in genetic disorders such as Fanconi anemia and Down's syndrome (6). SV40-infected cells from Fanconi anemia patients also express SV40 T-antigen more frequently than cells from normal individuals (3,7). Since the incidence of SV40 T-antigen is correlated with the incidence of colony formation (3, 7, S), the relatively short-term immunofluorescent T-antigen assay (requiring 3 days of incubation) may be more easily applied to large populations than the tedious transformation assay requiring 21 days of incubation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other balanced translocations in A-T or A-T heterozygote cells did not cause raised transformation rates, so the presence of a clone per se does not appear to predispose the cell line to transformation, although it is possible to envisage that specific translocations may exert an effect. Potter and Potter (1975) found certain trisomic cells to be susceptible to SV40 transformation while others were not.…”
Section: Infection With Sv40 Dnamentioning
confidence: 99%
“…There are some suggestions that cells from these groups of patients are more susceptible to transformation by SV40 virus (e.g. Potter & Potter 1975). However, the low level of this increased susceptibility and the variability of this test leaves room for doubt that this is necessarily a demonstration of the underlying mechanism of susceptibility.…”
Section: Constitutional Chromosome Abnormalitiesmentioning
confidence: 99%